Screening and comparative production of cellulases by local penecillium isolates and trichoderma Reesei Rut C30 - Cruz, Wilma T. (1988)
A thousand and sixty-two fungal isolates obtained from various sources were screened for extracellular production. The top four producers identified as Penicillium spp. were found to produce significantly higher B-glucosidase levels compared with the control strain. Trichoderma reesei Rut C30 on all substrates tested: rice straw. rice hull, corn cob, corn stalk and corn dust. All fungal strains showed variation on the levels and ratios of their cellulase components. (CMCase, FPase ans B-glucosidase) produced on different substrates.
Includes bibliographical references (page 108)
Keywords: Biochemistry; Cellulases, production; Penecillium Isolates; Trichoderma Reesei Rut C30.